2014
DOI: 10.1016/j.actamat.2014.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of compression–tension asymmetry in plasticity of Fe nanopillars

Abstract: Tension-compression asymmetry is a notable feature of plasticity in bcc single crystals. Recent experiments reveal striking differences in the plasticity of bcc nanopillars for tension and compression. Here we present results from molecular dynamics simulations of nanopillars of bcc Fe in tension and compression. We find that a totally different deformation mechanism applies in each cases: dislocation glide in compression and twinning in tension. This difference explains experimentally-observed asymmetry in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 34 publications
10
57
1
Order By: Relevance
“…3 Mo1-Engineering stress versus engineering strain curves obtained from the experimental test campaign (the average curve is shown for each testing condition): a compression tests at room temperature varying the strain-rate; b tensile tests at room temperature varying the strain-rate; c quasi-static tensile tests varying the temperature; d tensile tests in dynamic loading condition varying the temperature tension, it is possible to notice that the material strength is higher in compression. The same result was found also in [10][11][12][13][14]. As well known, this is the typical behavior expected for BCC metals and it was previously notice precisely on molybdenum.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…3 Mo1-Engineering stress versus engineering strain curves obtained from the experimental test campaign (the average curve is shown for each testing condition): a compression tests at room temperature varying the strain-rate; b tensile tests at room temperature varying the strain-rate; c quasi-static tensile tests varying the temperature; d tensile tests in dynamic loading condition varying the temperature tension, it is possible to notice that the material strength is higher in compression. The same result was found also in [10][11][12][13][14]. As well known, this is the typical behavior expected for BCC metals and it was previously notice precisely on molybdenum.…”
Section: Resultssupporting
confidence: 75%
“…[8,9], also the effect of the irradiation was investigated and modelled. Finally, considering the results reported in [10][11][12][13][14], an asymmetric behavior is expected in compression and tension tests: this was a general characteristic of BCC metals and it was previously noticed on molybdenum. In a lot of the available works, the data were used to calibrate strength models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Under tensile loading, BCC Fe nanowires oriented in <100>, <112> and <102> axial directions deform predominantly by the twinning mechanism, whereas the full dislocation slip has been observed in <110> and <111> orientations 8 . Further, it has been shown that BCC Fe nanowires exhibit tension-compression asymmetry in deformation mechanisms 8,9 . In contrast to tensile loading, the nanowire with <100> orientation deformed by the dislocation slip, whereas twinning was observed in <110> orientation under compressive loading [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Further, it has been shown that BCC Fe nanowires exhibit tension-compression asymmetry in deformation mechanisms 8,9 . In contrast to tensile loading, the nanowire with <100> orientation deformed by the dislocation slip, whereas twinning was observed in <110> orientation under compressive loading [8][9][10] . Recently, Wang et al 11 have provided the first experimental evidence of deformation twinning in BCC W nanowires with 15 nm diameter thereby conforming the predictions made using MD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation